Impact of virtual water flow with the energy product transfer on sustainable water resources utilization in the main coal-fired power energy bases of Northern China. (October 2018) - Gao, Xuerui; Chen, Qianyun; Lu, Shibao; Wang, Yubao; An, Tingli; Zhuo, La; Wu, Pute
Abstract: To analyze the water security status and propose the countermeasures, this study calculated the total water consumption of the energy products focusing on coal mining and coal-fired electricity generation and explored the changing characteristics of the total water footprint in the period of 2006-2015, and also revealed the virtual water flowing patterns embedded in coal and electricity transfer among different regions of China. The results show that the annual total water footprint of coal and coal-fired electricity is as much as 1.05 billion m 3, accounting for 22.8 % of the total fresh available water resources in the nine energy bases. The total virtual water flowing out of the nine energy bases embedded in energy product trade is keeping increasing in the period of 2006-2015, with the growth rate of 3.03×10 7 m 3 /a. In 2015, the total virtual water flowing out is as much as 9.57×10 8 m 3, accounting for 81.2 % of the total water footprint of coal and electricity in the nine bases. And the water stress indices in the above nine bases are also showing an obvious increasing trend in the past decade. Coal and coal-fired electricity production consume much water in the arid and semi-arid energy bases, which poses great negative impact on the local water system and ecosystem. To control the water consumption of energy sector, improve water using efficiency and adjust the industrial structure should be continuously implemented in the future.